Management of acute pancreatitis. (August 2014) - Goldenberg, David E; Gordon, Stuart R; Gardner, Timothy B
<x xml:space="preserve">Abstract</x> Acute pancreatitis (AP) is a common medical condition with extensive morbidity and mortality. Approximately 210, 000 Americans are hospitalized each year; and 5% of patients with AP will die. It is also an expensive condition, costing 2.6 billion dollars (United States) in 2009 alone. Moreover, the incidence is increasing – the National Hospital Discharge Survey showed hospitalizations increased from 78 per 100, 000 in 2007 to 90 per 100, 000 just three years later in 2010. There is no proven pharmacologic entity to treat the inflammatory response associated with acute pancreatitis; supportive care with IV fluids, bowel rest and pain control are the mainstays of therapy. Recently, new developments to help increase survival and minimize morbidity with several key interventions have been investigated. This summary highlights new studies and meta-analyses to provide current opinion on treatment of this morbid condition.